Avaliação clínica do íleo pós-operatório após nutrição enteral precoce em cirurgias do trato digestório alto - Bernardes, Liandra Freitas Marquez (2006)
It is common that feeding after gastric and bowel surgeries takes place only after postoperative ileus resolution. Early enteral nutrition has showed advantages as faster gastric and bowel motility recovery, smaller hospital stay periods and best nitrogen balance. The aim of this study is to show that early feeding propitiates these advantages in addition to be tolerable. Patients submitted to upper digestive tract surgeries were distributed in two casual groups: the control group received oral diet after 72 hours after surgery/ and the study group, with enteral nutrition introduced by a nasoenteric catheter 24 hours after surgery. Abdomen diameter and aspect; bowel sounds; flatus and stools elimination; regurgitation, diarrhea, abdominal pain, nausea and vomits presence or absence data were collected everyday . Nitrogen balance was measured in all patients on the fourth postoperative day. Discharge from hospital was measured too. Patients in the study group (8) and the control group (8) presented no difference concerning to hospital stay, postoperative ileus recovery period and diet tolerance. Nitrogen balance was statistically significant (p<0,000) and showed better results in the study group. Early enteral nutrition introduction after upper digestive tract surgeries is tolerated and it allows a better balanced nitrogen.